In Brief: Laboratory and clinical monitoring requirements for JAK inhibitors (Canadian Dermatology Today, 2023)
Janus kinase (JAK) inhibitors, more commonly referred to as JAK inhibitors (JAKi), are a class of drugs that target and block the JAK- signal transducer and activator of transcription (STAT) pathway, allowing regulation of immune responses and cell proliferation. The JAK-STAT pathway is found in many immune cells and is known to augment the signal from cytokine receptors at the cell’s surface to induce the transcription of messenger RNA in the nucleus. The key protein-encoding genes in this pathway were identified using primers to amplify, from the DNA of lymphoid tissue, a conserved kinase domain that phosphorylates tyrosine residues on substrate proteins. This eventually led to the discovery of 4 related protein tyrosine kinases (PTKs): JAK1, JAK2, JAK3 and tyrosine kinase 2 (TYK2).